Comparison of hemostatic agents in patients with spontaneous intracerebral hemorrhage: A protocol for a network meta-analysis. Issue 43 (23rd October 2020) - Li, Yujian; Zheng, Jun; Zhou, Huiqing; Yang, Xiang; Li, Hao
Abstract: Background: Spontaneous intracerebral hemorrhage (sICH) is a serious stroke subtype. The effective therapies for patients with sICH are still unclear, and the role of hemostatic agents in sICH is still unclear. Although some studies have shown that hemostatic agents could benefit patients with sICH, different hemostatic drugs have different effects on patients with sICH, and which hemostatic drug has the best effect on the prevention of hematoma expansion and neurological deterioration in sICH patients remains unclear. To better understand the effects of hemostatic agents in patients with sICH, it is necessary to carry out a network meta-analysis to comprehensively compare the effects of different hemostatic agents. Methods: This protocol has been designed following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols statement. Related studies in the following databases will be searched until September 2020: PubMed, Embase, Scopus, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, VIP and Wanfang. Randomized controlled trials and nonrandomized controlled studies comparing at least 2 different hemostatic agents in sICH patients will be included. A quality assessment will be conducted with the Cochrane Collaboration tool or the Newcastle-Ottawa Scale based on the study design. The primary outcome will be the incidence of hematoma expansion, and the secondary outcome will be the functional outcome. Pairwise and network meta-analyses will be conducted using STATA V.14 (StataCorp, College Station, Texas, USA). Mean ranks and the surface under the cumulative ranking curve will be used to evaluate every agent. Statistical inconsistency assessment, subgroup analysis, sensitivity analysis and publication bias assessment will be performed. Results: According to disseminate through academic conferences, the results of this network meta-analysis are expected to publish in a peer-reviewed journal. Conclusion: This study will provide high quality evidence about effects of different hemostatic agents in patients with sICH. Registration number: CRD42020196039. Abstract : Supplemental Digital Content is available in the text